2D Metal–Organic Frameworks: Ultrathin 2D Cobalt Zeolite‐Imidazole Framework Nanosheets for Electrocatalytic Oxygen Evolution (Adv. Sci. 11/2018). Issue 11 (21st November 2018) - Jayaramulu, Kolleboyina; Masa, Justus; Morales, Dulce M.; Tomanec, Ondrej; Ranc, Vaclav; Petr, Martin; Wilde, Patrick; Chen, Yen‐Ting; Zboril, Radek; Schuhmann, Wolfgang; Fischer, Roland A.
Abstract : In article number1801029, Kolleboyina Jayaramulu, Justus Masa, Wolfgang Schuhmann, Roland A. Fischer, and co‐workers report simple and facile synthesis of cobalt‐based 2D zeolite imidazole framework nanosheets [Co‐ZIF‐9(III)] by mechano‐chemical grinding with subsequent liquid‐phase exfoliation. The resultant 2D material exhibits highly efficient oxygen evolution reaction (OER) activity under alkaline conditions, attributed to increased accessibility of redox‐active cobalt oxyhydroxide active sites with a nitrogen coordination environment N4 CoOOH, and efficiently mimics Co‐Porphyrin electrocatalysts.